Biopolymers extracted from agro-industrial wastes of lucuma, avocado and rice for production of biodegradable trays - Laydy Mitsu Mena-Chacon; Luz Quispe-Sanchez; Fiorella Chicana; Robin Oblitas; Angel Fernando Huaman-Pilco; Sandra Mori; Manuel Oliva; Ives Yoplac (Journal of Agriculture and Food Research, 2025)
Biopolymers derived from agro-industrial wastes — lucuma seed starch, avocado seed starch, and rice husk fibers — were investigated for their potential use in developing biodegradable trays. Avocado seed starch exhibited the greatest concentration of amylose (30.87 %) and the minimal protein content (2.31 %), with a reddish tone was likely linked to bioactive compounds. Its starch granules presented an oval shape (26.97 × 11.74 μm), larger than the predominantly polyhedral granules of lucuma seed starch (9.87 μm). The highest amylose content was associated with larger values of gelatinization (T0 67.78 °C, Tp 73.90 °C, Tc 78.36 °C), hardness (24.62 N), cohesion (0.64), and gumminess (18.93 N). FT-IR analysis of rice husk displayed characteristic peaks associated with the presence of cellulose, hemicellulose, lignin, and silica. Potato starch was partially substituted with lucuma and avocado seed starches and reinforced with rice husk fibers to produce biodegradable trays via thermo-pressing. Adding rice husk fibers reduced expansion of starch, thereby making the internal structure of trays more compact and improving their physicochemical and mechanical properties. The incorporation of fibers increased the browning rate, especially those containing avocado or lucuma seed starch, probably associated with the residual phenolic compounds in starches, which are prone to oxidation, caramelization, and Maillard reaction during thermo-pressing. While all trays demonstrated high rate of biodegradation within 28 days (minimum 80.29 %), higher fiber content reduced the degradation rate due to the structural stability imparted by cellulose. This study highlights the potential of underutilized agro-industrial by-products in advancing sustainable food packaging solutions under circular economy focus.